National Survey of Radiation Doses of Pediatric Chest Radiography in Korea: Analysis of the Factors Affecting Radiation Doses - Kim, Bo Hyun; Do, Kyung-Hyun; Goo, Hyun Woo; Yang, Dong Hyun; Oh, Sang Young; Kim, Hyeog Ju; Lee, Kwang Yong; Lee, Jung Eun (Korean journal of radiology, 2012)
To investigate radiation doses in pediatric chest radiography in a national survey and to analyze the factors that affect radiation doses. The study was based on the results of 149 chest radiography machines in 135 hospitals nationwide. For each machine, a chest radiograph was obtained by using a phantom representing a 5-year-old child (ATOM® dosimetry phantom, model 705-D, CIRS, Norfolk, VA, USA) with each hospital's own protocol. Five glass dosimeters (M-GD352M, Asahi Techno Glass Corporation, Shizuoka, Japan) were horizontally installed at the center of the phantom to measure the dose. Other factors including machine's radiography system, presence of dedicated pediatric radiography machine, presence of an attending pediatric radiologist, and the use of automatic exposure control (AEC) were also evaluated. The average protocol for pediatric chest radiography examination in Korea was 94.9 peak kilovoltage and 4.30 milliampere second. The mean entrance surface dose (ESD) during a single examination was 140.4 microgray (µGy). The third quartile, median, minimum and maximum value of ESD were 160.8 µGy, 93.4 µGy, 18.8 µGy, and 2334.6 µGy, respectively. There was no significant dose difference between digital and non-digital radiography systems. The use of AEC significantly reduced radiation doses of pediatric chest radiographs (p < 0.001). Our nationwide survey shows that the third quartile, median, and mean ESD for pediatric chest radiograph is 160.8 µGy, 93.4 µGy, and 140.4 µGy, respectively. No significant dose difference is noticed between digital and non-digital radiography systems, and the use of AEC helps significantly reduce radiation doses.